Essential updates 2018/2019: Current topics in the surgical treatment of pancreatic ductal adenocarcinoma. Issue 1 (9th August 2020) - Ishido, Keinosuke; Hakamada, Kenichi; Kimura, Norihisa; Miura, Takuya; Wakiya, Taiichi
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is highly malignant. While cancers in other organs have shown clear improvements in 5‐year survival, the 5‐year survival rate of pancreatic cancer is approximately 10%. Early relapse and metastasis are not uncommon, making it difficult to achieve an acceptable prognosis even after complete surgical resection of the pancreas. Studies have been performed on various treatments to improve the prognosis of PDAC, and multidisciplinary approaches including non‐surgical treatments have led to gradual improvement. In the present literature review, we have described the significance of anatomical and biological resectability criteria, the concept of R0 resection in surgical treatment, the feasibility of minimally invasive surgery, the remarkable development of perioperative chemotherapy, the effectiveness of conversion surgery for unresectable PDAC, and ongoing challenges in PDAC treatment. We also provide an essential update on these subjects by focusing on recent trends and topics. Abstract : In the present literature review, we have described the significance of anatomical and biological resectability criteria, the concept of R0 resection in surgical treatment, the feasibility of minimally invasive surgery, the remarkable development of perioperative chemotherapy, the effectiveness of conversion surgery for unresectable pancreatic cancer, and ongoing challenges in pancreatic cancer treatment. We also provide an essential update on these subjects by focusing on recent trends and topics.